1961
DOI: 10.1037/h0045020
|View full text |Cite
|
Sign up to set email alerts
|

Concept attainment: I. The role of age and intelligence in concept attainment by induction.

Abstract: Most concept studies with children have utilized either the interviewquestionnaire method or the performance method (Vinacke, 1952, p. 108).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
1

Year Published

1966
1966
1982
1982

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 32 publications
2
10
1
Order By: Relevance
“…However, the results obtained herein agreed with relationships reported by Long and Welch (1942) who studied intellectually superior Ss at several age levels and Osler and Fivel (1961) who studied intellectllally superior and normal Ss at several age levels. Generally, these pairs of investigators observed that their Ss attained concepts with similar facility at two levels of inclusiveness corresponding to the levels used in the present study; they observed this similarity when words as well as pictures were used to portray specific instances.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the results obtained herein agreed with relationships reported by Long and Welch (1942) who studied intellectually superior Ss at several age levels and Osler and Fivel (1961) who studied intellectllally superior and normal Ss at several age levels. Generally, these pairs of investigators observed that their Ss attained concepts with similar facility at two levels of inclusiveness corresponding to the levels used in the present study; they observed this similarity when words as well as pictures were used to portray specific instances.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study did not disagree with results reported by investigators who used concrete and semi-concrete materials: Johnson and Blake (1960) and Martin and Blum (1961) who observed that retarded and normal Ss equated for MA did not differ in concept attainment; Osler and Fivel ( 1961) who found that the concept attainment of superior Ss exceeded that of normal Ss who had similar CAs.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The suggestion is made that previous jindings which report a A number of studies have found that, under some conditions at least, the mean number of errors to criterion in concept attainment is greater for lower-IQ children than for children ofhigher IQ (e.g., Osler & Fivel, 1961;Osler&Trautman, 1961;Wolff, 1967). These results have typically been interpreted as indicating that lower-IQ ehildren take longer to solve the eoneepts.…”
mentioning
confidence: 80%
“…In aseries of studies relating intelligence to concept learning, Osler and associates found that: (1) Ss of superior intelligence solve concepts more rapidly than lower·intelligence Ss; and (2) high·intelligence Ss learn insightfully, whereas lower-intelligence Ss learn by associative incremental learning (Osler & Fivel, 1961;Osler & Trautman, 1961;Osler & Weiss, 1962). In contrast, recent studies (Harnilton & Saltz, 1969; have found that: (I) when precriterion errors for concept solvers are Vincentized into quartiles no evidence of precriterion improvement is found for Ss of high or lower intelligence, and (2) intelligence is related to the frequency with which Ss solve problems but not to the speed of solution among the solvers.…”
mentioning
confidence: 99%